Behavioral inhibition and activation as a modifier process in autism spectrum disorder: Examination of self‐reported BIS/BAS and alpha EEG asymmetry. Issue 12 (26th November 2018) - Schiltz, Hillary K.; McVey, Alana J.; Barrington, Alexander; Haendel, Angela D.; Dolan, Bridget K.; Willar, Kirsten S.; Pleiss, Sheryl; Karst, Jeffrey S.; Vogt, Elisabeth; Murphy, Christina C.; Gonring, Kelsey; Van Hecke, Amy Vaughan
Abstract : The Modifier Model of autism spectrum disorder (ASD) suggests that phenotypic variability within ASD is rooted in modifier processes, such as the behavioral inhibition system (BIS) and behavioral activation system (BAS). Among a sample of 53 adolescents with ASD, this study examined associations between (a) self‐reported BIS/BAS and frontal and parietal alpha electroencephalogram asymmetry and whether these indices related to (b) ASD severity (via the Autism Quotient), and/or (c) co‐occurring anxiety and attention‐deficit hyperactivity disorder (via Youth Self Report and Child Behavior Checklist). Findings showed that alpha asymmetry was associated with self‐reported BAS scores, such that greater BAS was related to greater right‐frontal hemisphere activation and relatively greater left‐parietal hemisphere activation. Additionally, associations emerged between ASD severity and self‐reported BAS and alpha asymmetry, and between anxiety symptoms and self‐reported BIS and alpha asymmetry. Furthermore, mediation analyses revealed that BAS mediated the association between asymmetry and autism severity. Therefore, alpha asymmetry and BIS/BAS activity may provide insight into how ASD presents in adolescence as well as who might be at greater risk for developing co‐occurring psychopathologies. This study highlights the importance of considering motivational systems to elucidate individual differences among youth with ASD and working toward the longer term goal of better understanding differential responses to treatment. Autism Research 2018, 11: 1653–1666 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Differences in the likelihood to avoid (behavioral inhibition system; BIS) or approach (behavioral activation system; BAS) situations are thought to relate to patterns of brain activity (via electroencephalogram asymmetry asymmetry). This study revealed that these tendencies may influence the presentation of autism spectrum disorder (ASD) and symptoms of anxiety in adolescents with ASD.